Implikasi Pajak Penghasilan Atas Revaluasi Aktiva Tetap PT. Sinar Mentari Raya - Manubulu, Herry Aprilia; Faimnasi, Agustina (Politeknik Negeri Ambon, 2024)
This research was conducted using a qualitative approach and an explanatory form with the aim of explaining the process of revaluation of fixed assets at PT Sinar Mentari Raya and its income tax implications. The results showed, First, the process of revaluation of fixed assets at PT Sinar Mentari Raya in 2021 was carried out with consideration of the need to improve the company's financial performance. The valuation is carried out using appraisal services using the income approach and cost approach to revalue fixed assets in the form of vehicles and production machinery. The result of the revaluation of fixed assets at PT Sinar Mentari Raya is the difference over the revaluation of fixed assets. Second, the income tax implications of the revaluation of fixed assets carried out by PT Sinar Mentari Raya have an impact on the depreciation expense of fixed assets according to the tax burden in 2021. Depreciation expense according to the fiscal that must be recognized by the company cannot change as depreciation according to accounting that has changed its depreciation basis after the revaluation of fixed assets. Depreciation expense remains the same as the previous year, resulting in a positive fiscal correction that increases the amount of taxable income. Third, the revaluation of fixed assets for tax purposes if carried out by PT Sinar Mentari Raya in 2021 must be carried out as stipulated in PMK number 79 of 2008. Keywords: Income Tax, Revaluation of Fixed Assets